Implementation of the 2013 Curriculum in Shaping the Character of Learners - Lailia Rahman, Marita; Mufron, Ali; Agustina Nurlaila Eka Erfiana, Nita (CV. Inara, 2021)
This study stems from the moral decline that occurs in the younger generation. Many cases of juvenile delinquency are carried out by learners such as bullying, drugs, fighting between students and so on. The implementation of the curriculum in educational institutions needs to be emphasized on character assistance, so that learners are expected to have good character. The focus of this research is how the vision, mission, and objectives of the institution in shaping the character of learners. How to construct the character-based learning process in shaping the character of learners. How to internalize character values in shaping the character of learners.The research method used is qualitative research with data collection techniques using interviews, observations, and documentation. The conclusion of this research is thatthe vision, mission, and objectives of the institution develop in programmatic activities, construct the institution's curriculum with scientific and paikem approaches, internalize character values in teaching and learning activities also intra- and extra-curricular activities.